TEACHER’S TECHNIQUES ON PROVIDING WRITTEN FEEDBACK TO STUDENTS’ WRITING COMPOSITION (RETAIN, 2017)
TEACHER’S TECHNIQUES ON PROVIDING WRITTEN FEEDBACK TO STUDENTS’ WRITING COMPOSITION Rismi Wulandari English Department, Faculty of Langauge and Art, State University of Surabaya rismiwulandari@gmail.com Prof. Dr. Susanto, M.Pd. English Department, Faculty of Langauge and Art, State University of Surabaya susantoniki@gmail.com Abstrak Siswa membutuhkan banyak bantuan dan umpan balik dari guru mereka terutama dalam menunjukkan kesalahan yang mereka buat. Dalam hal ini, umpan balik sebagai strategi yang diterapkan oleh guru merupakan strategi memperbaiki kesalahan siswa. Pada dasarnya, preferensi guru untuk umpan balik yang diberikan pada karangan siswa bergantung pada pengalaman dan persepsi guru sendiri. Dari pernyataan tersebut, dapat disimpulkan bahwa ada banyak kemungkinan bahwa guru yang berbeda menggunakan strategi yang berbeda dalam memberikan umpan balik. Berkenaan dengan masalah tersebut, peneliti mempertimbangkan untuk melakukan penelitian yang dimaksudkan untuk menganalisis jenis umpan balik guru pada karangan siswa. Penelitian ini dirancang berdasarkan penelitian interpretatif dasar. Subjek penelitian ini adalah seorang guru bahasa Inggris yang memberikan umpan balik terhadap komposisi siswa di salah satu Sekolah Menengah Atas favorit di Jawa Timur. Dalam penelitian ini, data tersebut merupakan umpan balik tertulis guru dalam komposisi siswa. Peneliti mengumpulkan data dengan mendapatkan dari guru, sehingga peneliti sendiri adalah kunci instrumen penelitian ini. Hasil penelitian ini menunjukkan bahwa guru menggunakan empat jenis umpan balik korektif tertulis dan komentar tertulis. Sebagian besar umpan balik dari guru merupakan indirect corrective feedback, sementara direct corrective feedback adalah yang paling sedikit. Dalam metalinguistic feedback, guru tersebut memberi petunjuk linguistik untuk memperbaiki kesalahan tersebut. Namun, faktanya, siswa tersebut tidak merevisi kesalahan seperti yang disarankan guru dalam metalinguistic feedback. Peneliti juga menemukan bahwa guru memusatkan perhatian pada kesalahan spesifik dan mengabaikan kesalahan lainnya. Kemudian, di akhir karangan siswa, guru juga memberi arahan agar siswa lebih memperhatikan kesalahan pada pronoun. Dia telah menulis written commentary tentang pronoun tersebut. Kata Kunci: umpan balik secara tertulis, karangan siswa. Abstract Students need a lot of assistance and feedback from their teachers especially in pointing out the errors that they make. In this case, feedback as strategy applied by the teacher is the important position to improve the students errors. Basically, teachers’ preferences for feedback given to the students’ performances are depend on the teachers’ own experiences and perceptions. From those statements, it can be inferred that there are wide probabilities that different teachers use different strategies on providing feedback as they are influenced by their practices. In regard to the fact that different teachers use different strategies on providing feedback, the researcher considered to conduct a study that is intend to analyze the types of teacher feedback on the students’ essay writing composition. This study was designed based on basic interpretative research. The subject of this study was an English teacher who gave feedback to the students’ composition in one of favorite Senior High School in East Java. In this research, the data were teacher’s written feedback in the students’ composition. The researcher collected the data by obtaining from the teacher, thus the researcher herself was the instrument key of this study. The results of this study showed that the teacher use four kind of written corrective feedback and a written commentary. Most type of feedback that the teacher use was indirect corrective feedback while direct corrective feedback was the least one. The teacher promoted the student to do self-correction by gave indirect corrective feedback. In metalinguistic feedback, the teacher gave linguistic clue to correct the errors. Then, in the end of student’s composition, the teacher also gave a direction to make the student pay more attention to her pronoun errors. She provided written commentary by drew a table of pronoun because most student’s errors occurred on the pronoun. Keywords: written feedback, student’s composition.